Plausibility of Menstrual Cycle Apps Claiming to Support Conception - Freis, Alexander; Freundl-Schütt, Tanja; Wallwiener, Lisa-Maria; Baur, Sigfried; Strowitzki, Thomas; Freundl, Günter; Frank-Herrmann, Petra (Frontiers in Public Health, 2018)
The interval of peak fertility during the menstrual cycle is of limited duration, and the day of ovulation varies, even in women with fairly regular cycles. Therefore, menstrual cycle apps identifying the “fertile window” for women trying to conceive must be quite precise. A deviation of a few days may lead the couple to focus on less- or non-fertile days for sexual intercourse and thus may be worse than random intercourse. The aim of the present investigation was to develop a scoring system for rating available apps for determining the fertile window and secondarily pilot test 12 apps currently available in both German and English (consisting of 6 calendar-based apps: Clue Menstruations- und Zykluskalender, Flo Menstruationskalender, Maya-Mein Periodentracker, Menstruationskalender Pro, Period Tracker Deluxe, and WomanLog-Pro-Kalender; 2 calculothermal apps: Ovy and Natural Cycles; and 4 symptothermal apps: myNFP, Lady Cycle, Lily, and OvuView). The calendar-based apps were investigated by entering several series of cycles with varying lengths, whereas the symptom-based apps were examined by entering data of cycles with known temperature rise, cervical mucus pattern, and clinical ovulation. The main criteria for evaluating the cycle apps were as follows: (1) What methods/parameters were used to determine the fertile window? (2) What study results exist concerning that underlying method/parameters? (3) What study results exist concerning the app itself? (4) Was there a qualified counseling service? The calendar-based apps predicted the fertile days based on data of previous cycles. They obtained zero points in our scoring system, as they did not comply with any of the evaluated criteria. Calculothermal apps had similar deficits for predicting the most fertile days and produced suboptimal results (Ovy 3/30 points and Natural Cycles 2/30 points). The symptothermal apps determined the fertile days based on parameters of the current cycle: Lady Cycle scored 20/30 points, myNFP 20/30 points, Lily 19/30 points, and OvuView 11/30 points. We concluded that the available cycle apps vary according to their underlying scientific quality and clear rating criteria have been suggested. Three of the tested apps were judged to be eligible for further study. The scientific evaluation of cycle apps depends on good prospective studies undertaken by independent investigators who are free of commercial bias.